2019
DOI: 10.1159/000502744
|View full text |Cite
|
Sign up to set email alerts
|

Complications after Radiofrequency Ablation for Hepatocellular Carcinoma: A Multicenter Study Involving 9,411 Japanese Patients

Abstract: <b><i>Introduction:</i></b> Radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC) is considered a safe and minimally invasive procedure. We previously reported that the mortality and complication rates for RFA were 0.038% (5/13,283 patients) and 3.54% (579 complications/16,346 procedures), respectively, from 1999 to 2010 (previous period). In this study, we investigated the clinical criteria for RFA and the mortality and complication rates from 2011 to 2015 (recent period). &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 33 publications
3
40
1
Order By: Relevance
“…There were two patients occurred major complications after RFA, one developed symptomatic pleural effusion and required percutaneous drainage and of the other developed liver abscess. Liver abscess is a rare complication of RFA for HCC [31]. Patients with Roux-en-Y reconstruction may be at elevated risk of infection [32].…”
Section: Discussionmentioning
confidence: 99%
“…There were two patients occurred major complications after RFA, one developed symptomatic pleural effusion and required percutaneous drainage and of the other developed liver abscess. Liver abscess is a rare complication of RFA for HCC [31]. Patients with Roux-en-Y reconstruction may be at elevated risk of infection [32].…”
Section: Discussionmentioning
confidence: 99%
“…RFA is considered the standard treatment for HCC worldwide for patients with <3 tumors that are <3 cm in diameter [ 13 , 14 ]. Maeda et al [ 15 ] reported that among 11,298 RFA procedures, only 330 complications (2.92%) were identified. Six patients (0.064%) died from RFA-related complications during the recent period (2011–2015), and according to quality improvement guidelines for RFA of liver tumors, RFA is contraindicated for the treatment of tumors located <1 cm from the main biliary duct or a bilioenteric anastomosis [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, the indications for RFA in patients with HCC tumors adjacent to the first or second branches of the bile duct have increased from 15 of 20 centers (75%) during the previous period (1999–2010) to 21 of 25 centers (84%) during the recent period. Indications have also increased for patients with a tumor near a bilioenteric anastomosis or papillary dysfunction from 5 of 20 centers (25%) during the previous period to 10 of 25 centers (40%) during the recent period, which has consequently increased performance of bile duct cooling via a nasobiliary drainage tube from 25 to 32% [ 15 ]. Ohnishi et al [ 10 ] reported the utility of intraductal chilled saline perfusion (ICSP) to prevent bile duct injury during percutaneous RFA for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…2 Similarly, in 2020 Maeda et al reported a complication rate of 2.9% in 9,411 patients. 3 Recognised complications include haemorrhage, abscess formation, biliary fistulation, and hepatic injury. As more cases are performed, rarer complications are being identified, one of which is diaphragmatic injury.…”
Section: Introductionmentioning
confidence: 99%